2020
DOI: 10.1101/2020.02.04.20020339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population movement, city closure and spatial transmission of the 2019-nCoV infection in China

Abstract: 16The outbreak of pneumonia caused by a novel coronavirus (2019-nCoV) in Wuhan 17City of China obtained global concern, the population outflow from Wuhan has 18 contributed to spatial expansion in other parts of China. We examined the effects of 19 population outflow from Wuhan on the 2019-nCoV transmission in other provinces 20 and cities of China, as well as the impacts of the city closure in Wuhan. We observed 21 a significantly positive association between population movement and the number of 22 cases. F… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…The timing and location of the outbreak facilitated the rapid transmission of the virus within a highly mobile population. The initial reporting of observed cases occurred during the traditional Chinese New Year, when the largest population movement takes place every year (Ai et al, 2020). Further, Wuhan is a highly populated city with more than 11 million residents and is connected to many cities in China through public transportation, such as buses, trains, and flights (Lai et al, 2020;Read, Bridgen, Cummings, Ho, & Jewell, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The timing and location of the outbreak facilitated the rapid transmission of the virus within a highly mobile population. The initial reporting of observed cases occurred during the traditional Chinese New Year, when the largest population movement takes place every year (Ai et al, 2020). Further, Wuhan is a highly populated city with more than 11 million residents and is connected to many cities in China through public transportation, such as buses, trains, and flights (Lai et al, 2020;Read, Bridgen, Cummings, Ho, & Jewell, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The best available scientific evidence is therefore required to design effective NPI strategies and disseminate this knowledge urgently to help policy makers assess the potential benefits and costs of NPIs to contain COVID-19 outbreaks. Some previous studies have preliminarily explored the lockdown of Wuhan, [25][26][27] travel restrictions, [28][29][30] airport screening, 31,32 and the isolation of cases and contact tracing for containing virus transmission, respectively. 33,34 The conclusions of these studies are persuasive, there are still key knowledge gaps on the effectiveness of different interventions.…”
Section: Introductionmentioning
confidence: 99%
“…On Feb.9, 2020, X. Li et al [8] simulated the dynamics of the 2019-nCOV (COVID-19), on account of the strict control measures in Wuhan and Beijing. They showed that after the the traffic blockage on Jan.23,2020, the reproductive number in Wuhan will be 2.5, significantly lower than before.…”
Section: Introductionmentioning
confidence: 99%